2002
DOI: 10.1542/peds.109.1.e9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diabetes on Learning in Children

Abstract: ABSTRACT. Objective. Subtle neuropsychological deficits have been found in some children with type 1 diabetes. However, these data have been inconsistent, and it is not clear what the impact of these deficits might be on the learning of children with diabetes over time. The purpose of this study was to determine whether type 1 diabetes significantly interferes with the development of functional academic skills. It was hypothesized that 1) children with type 1 diabetes would demonstrate deficits in academic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 33 publications
(40 reference statements)
5
78
0
5
Order By: Relevance
“…The result is supported by the findings of Melnyk et al (2006) and Trzesniewski et al (2006), which indicated that adolescents with lower self-esteem have poorer physical health as measured by number of days absent from school due to physical illness. Using number of days absent from school as an indicator for assessing children physical health status has been reported in previous literature (McCarthy, Lindgren, Mengeling, Tsalikian, & Engvall, 2002;Stein & Jessop, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The result is supported by the findings of Melnyk et al (2006) and Trzesniewski et al (2006), which indicated that adolescents with lower self-esteem have poorer physical health as measured by number of days absent from school due to physical illness. Using number of days absent from school as an indicator for assessing children physical health status has been reported in previous literature (McCarthy, Lindgren, Mengeling, Tsalikian, & Engvall, 2002;Stein & Jessop, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…For this sample, Pearson correlations between parent and teacher ratings on each scale were 0.403, 0.570, 0.288, and 0.224, respectively ( n = 78 with both forms). Parent and teacher forms have been used to assess PBS-30 factors in children with diabetes20,21 and attention-deficit/hyperactivity disorder 22…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes mellitus is sub-classified into type 1 (insulin-deficient) and type 2 (insulin-resistant) diabetes and cognitive deficits occur in both of these patient populations (Ryan et al, 1985; Rovet et al, 1987; Reaven et al, 1990; Ryan and Williams, 1993; McCarthy et al, 2002; Cukierman et al, 2005; Manschot et al, 2006; Biessels et al, 2008). Studies have found a relative risk of about 1.9 to 2.3 of developing AD for diabetic patients (Ott et al, 1996; Leibson et al, 1997; Ronnemaa et al, 2009), and this risk can increase up to 5.5 in the presence of Apo E4, a risk factor for AD (Peila et al, 2002).…”
Section: Insulinmentioning
confidence: 99%